PENGARUH JAMUR MIKORIZA ARBUSKULAR TERHADAP PERKEMBANGAN PENYAKIT BERCAK DAUN DAN PERTUMBUHAN TEBU PADA KONDISI KERING - , ADIK PIPIT APRILIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Arbuskular Mycorrhizal Fungi (AMF) reffer to endomycorrhiza that can systematically or locally enhance of plants toward biotic and abiotic stress. The productivity of sugarcane plant will decrease due to drought, disturbance of leaf spot disease and limited farmland. It is expected that the presence of AMF able to increase the vegetative growth and hinder this disease. The study on effect of AMF on the growth of rust disease and the growth of sugarcane plant in dry condition was strarted from February to Agustus 2013, Arranged by a completely randomized design (CRD) with two factors and 3 replications. The first factor is isolate of AMF consisting of Klaten, Kulon Progo, Sleman, Batang, Bantul and without AMF. The second factor is the watering interval: 7 days and 2 days. The parameter measured includes the plant height, trunk diameter, number of leaves, number of tillers, greenness of leaf, the rate of photosynthesis, plant dry weight, number of spores, the percentage of mycorrhizal infection, disease intensity, and the disease infection rate. The results showed that the isolate of AMF can significantly enhace the plant height, trunk diameter, number of leaves, number of buds, greenness of leaf, the rate of photosynthesis, and dry weight of plant. The isolate of arbuscular mycorrhizal fungi is able to increased the parameter of vegetative growth in 7 days watering interval and not significantly different with 2 days watering interval. On the other hand, arbuscular mycorrhizal fungi can hinder the orange rust infection rate caused by Puccinia kuehnii at 7 days and 2 days watering interval. Using AMF is positively correlated to the increase of vegetative growth parameterâs and negatively correlated to the infection rate of orange rust disease.